2017
DOI: 10.18388/abp.2017_1618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic value of hTERT mRNA expression in patients with non-small-cell lung cancer

Abstract: Telomerase, undetectable in normal somatic cells, plays a critical role in carcinogenesis of the majority of human tumors including lung carcinoma. The aim of our study was to determine human telomerase reverse transcriptase (hTERT) mRNA expression in patients with non-small cell lung cancer (NSCLC) in order to estimate its usefulness as diagnostic and/or prognostic factor. hTERT expression was analyzed in a group of 12 females and 28 males with NSCLC using Quantitative Real-Time Polymerase Chain Reaction (QRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…An increasing amount of research has also focused on the relationship between the hTERT and non-small cell lung cancer. It has been reported that repression of hTERT promoted the prognosis of early stage non-small cell lung cancer [ 32 ]. However, understanding of the mechanism underlying hTERT involvement in the regulation of SCLC remains unclear to the best of our knowledge [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of research has also focused on the relationship between the hTERT and non-small cell lung cancer. It has been reported that repression of hTERT promoted the prognosis of early stage non-small cell lung cancer [ 32 ]. However, understanding of the mechanism underlying hTERT involvement in the regulation of SCLC remains unclear to the best of our knowledge [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tumor tissues have been identified by hTERT expression, and more than 85% of cancer cells contain genetic aberrations and hTERT overexpression ( 13 ). In this study, our data analysis led us to believe that hTERT is also increased in the patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MYC inhibition induced tumor regression in K-Ras-driven LC in mice as well as in p53-deficient animals [121], which suggests the contribution of MYC for the progression of these tumors. hTERT expression has been reported (33% to 94%) in NSCLCs with poorer overall survival at three years [122] and it was significantly higher in NSCLC when compared with non-tumor tissues [123]. Among NSCLCs, AdCs display an increased expression of hTERT when compared with SQCs [122].…”
Section: Pathogenesis Of Lung Cancermentioning
confidence: 97%